Some Predictors of Reading Habits of Preschool Educators, Primary and Secondary School Teachers - Pečjak, Sonja (Bralni vzori 2, 2025)
This paper present: (1) the presence of certain reading habits among education professionals—specifically, the frequency and average duration of reading during leisure time, as well as library visits for borrowing books; and (2) the predictors of these reading habits within specific groups of education professionals - preschool, primary school and secondary school teachers. Based on a sample of 1,391 professionals and data collected via an online questionnaire, we found that the largest proportion of respondents reported frequent reading in their free time, while the smallest group read rarely. However, the proportion of infrequent readers was significantly higher among preschool teachers compared to other groups. Most professionals reported reading for pleasure between 1 and 4 hours per week on average, with preschool teachers again showing a significantly higher proportion of those who dedicate the least amount of time to reading. Across all professional groups, reading interest and reading competence emerged as the strongest predictors of both the frequency and duration of leisure reading and library use. Among preschool teachers and their assistants, years of professional experience and childhood reading experiences were also significant predictors.